Lasers in glaucoma - Kumar, S (Nepalese Journal of Ophthalmology, 2010)
Use of lasers in the treatment of various types of glaucomas is an important aspect in ophthalmic practice. Both Argon and Yag lasers are now-a-days commonly used in the treatment of angleclosure and open-angle glaucomas. Besides this, more recently, Diode lasers are being used for the treatment of the glaucomas. Lasers are also being used in the management of intractable glaucomas which are not controlled by medication alone. In this review article, all these features have been highlighted. Keywords: Lasers; glaucoma DOI: 10.3126/nepjoph.v2i1.3705 Nep J Oph 2010;2(1) 51-58